PERSEPSI ORANG TUA TENTANG TUNTUTAN MEMBACA,MENULIS DAN BERHITUNG (CALISTUNG) PADA ANAK USIA DINI DI PAUD NURUL IKHSAN - Ade Kurniawati; Maulida Nur; Ibnu Sina; Inten Risna; Mohamad Bayi Tabrani (Jurnal Manajemen Pendidikan, 2026)
Early Childhood Education (ECE) is a fundamental stage in establishing the foundation for children’s holistic development. However, in practice, the demand for early literacy and numeracy skills reading, writing, and arithmetic remains a major concern among parents. This study aims to examine parents’ perceptions of early literacy and numeracy demands in early childhood and their implications for learning practices at PAUD Nurul Ikhsan. This research employed a qualitative descriptive approach. The participants were three parents of five year old children enrolled in PAUD Nurul Ikhsan, selected through purposive sampling. Data were collected through in-depth interviews and observations and analyzed using thematic analysis. The findings reveal that parents generally perceive early literacy and numeracy skills as key indicators of children’s academic readiness for primary school. Nevertheless, parents also demonstrate awareness of the importance of setting appropriate boundaries in academic demands, emphasizing that learning should be flexible, enjoyable, and aligned with children’s developmental stages. Various strategies were used by parents to stimulate early literacy and numeracy skills, ranging from home learning assistance to additional tutoring. The study also highlights the importance of collaboration between parents and teachers to prevent excessive academic pressure on children.